P.S. I loathe you : a Clique novel - Harrison, Lisi (New York : Little, Brown and Company, 2009)
When the Pretty Committee deems its boy-fast null and void, boy fever sweeps through BOCD. What better way to back handspring into new crush Dempsey's heart than cheer for him on the soccer field? And just like that, Massie forms BOCD's first cheerleading squad.
Ages 12 and up.
Keywords: Cliques (Sociology) -- Fiction; Fiction